The suffering of Sheikh Maruf Al-Nawdhi in his homeland through his systematic message to Sultan Salim the Ottoman - Sarbaz, prof.dr. Hassan (Sulaimani Journal for Humanities, 2026)
Sheikh Maruf al-Nawdhi lived in the late twelfth and early thirteenth centuries AH in Sulaymaniyah. The Sulaymaniyah brigade and its suburbs during this period were under the authority of the papal princes who were interested in science, religion and literature and served scholars and writers. This region hosted many scientific, religious and literary figures from the Shahrzuri, Barzanji, Chori, Qazlji and others. However, this region witnessed unrest and devastating wars between the Papal princes on the one hand and the Ottomans and Iranians on the other. The neighboring areas and some of them remained in their homeland and suffered what they suffered from the woes, disasters and hardships, including Sheikh Marouf Al-Nawdhi, who witnessed what the Papal Emirate suffered from ruin and destruction. In his poems and systems especially in his systematic letter to Sultan Selim the Ottoman. This research aims to benefit from the descriptive analytical method to study what Sheikh Maruf al-Nawdhi suffered in his homeland through his systematic letter to Sultan Salim al-Ottoman. From him the Sheikh. The results of the research indicate that the most important difficulties and hardships that Sheikh Marouf Al-Nawdhi suffered in his homeland is that he did not remain in Kurdistan peace and happiness and spread sedition and heresies and violated the sanctuaries and increased injustice, adultery and destruction. He migrated to Muhajir Ibrahim in Mecca, Jerusalem and Syria.
Keywords: Sheikh Maruf AlNawdhi; the Papal Emirate; Sultan Selim the Ottoman